Patient Perception of Treatment Burden is High in Celiac Disease Compared to Other Common Conditions - Shah, Sveta (2014)
INTRODUCTION: The only treatment for celiac disease (CD) is life-long adherence to a gluten-free diet (GFD). Noncompliance is associated with signs and symptoms of celiac disease, yet long-term adherence rates are poor. It is not known how the burden of the GFD compares to other medical treatments, and there are limited data on the socio-economic factors influencing treatment adherence. In this study we compared treatment burden and health state in CD compared with other chronic illnesses and evaluated the relationship between treatment burden and adherence. METHODS: A survey was mailed to participants with: CD, gastroesophageal reflux disease (GERD), irritable bowel syndrome (IBS), inflammatory bowel disease (IBD), hypertension (HTN), diabetes mellitus (DM), congestive heart failure (CHF), and end stage renal disease on dialysis (ESRD). Surveys included demographic information and visual analog scales measuring treatment burden, importance of treatment, disease-specific and overall health status. RESULTS: We collected surveys from 341 celiac and 368 non-celiac participants. Celiac participants reported high treatment burden, greater than participants with GERD or HTN and comparable to ESRD. Conversely, patients with CD reported the highest health state of all groups. Factors associated with high treatment burden in CD included poor adherence, concern regarding food cost, eating outside the home, higher income, lack of college education and time limitations in preparing food. Poor adherence in CD was associated with increased symptoms, income, and low perceived importance of treatment. DISCUSSION: Participants with CD have high treatment burden but also excellent overall health status in comparison with other chronic medical conditions. The significant burden of dietary therapy for celiac disease argues for the need for safe adjuvant treatment as well as interventions designed to lower the perceived burden of the GFD.